Reconciling safe planetary targets and planetary justice: Why should social scientists engage with planetary targets? - J. Gupta (Elsevier, 2021)
As human activity threatens to make the planet unsafe for humanity and other life forms, scholars are identifying planetary targets set at a safe distance from biophysical thresholds beyond which critical Earth systems may collapse. Yet despite the profound implications that both meeting and transgressing such targets may have for human wellbeing, including the potential for negative trade-offs, there is limited social science analysis that systematically considers the justice dimensions of such targets. Here we assess a range of views on planetary justice and present three arguments associated with why social scientists should engage with the scholarship on safe targets. We argue that complementing safe targets with just targets offers a fruitful approach for considering synergies and trade-offs between environmental and social aspirations and can inform inclusive deliberation on these important issues.